New Secure E-mail System Based on Bio-Chaos Key Generation and Modified AES Algorithm - Hoomod, Haider K; Radi, A M (Journal of physics. Conference series, 2018)
The E-mail messages exchanged between sender's Mailbox and recipient's Mailbox over the open systems and insecure Networks. These messages may be vulnerable to eavesdropping and itself poses a real threat to the privacy and data integrity from unauthorized persons. The E-mail Security includes the following properties (Confidentiality, Authentication, Message integrity). We need a safe encryption algorithm to encrypt Email messages such as the algorithm Advanced Encryption Standard (AES) or Data Encryption Standard DES, as well as biometric recognition and chaotic system. The proposed E-mail system security uses modified AES algorithm and uses secret key-bio-chaos that consist of biometric (Fingerprint) and chaotic system (Lu and Lorenz). This modification makes the proposed system more sensitive and random. The execution time for both encryption and decryption of the proposed system is much less from original AES, in addition to being compatible with all Mail Servers.